(untitled) (CAHIERS MAGELLANES-NS, 2024)
This paper addresses the need to give more importance to the development of the speaking skill in students, which is generally ignored at the undergraduate level. It is observed that an undergraduate in India, gets some opportunity to listen, read and write in English, but hardly any, to speak in English in the classroom. Whether this gap is due to the structure of the syllabus, the teaching methodology used or the activities and tasks the students are engaged in during the class hours require careful investigation. Whatever the reasons, it is clear that this trend, where the students do not get much opportunity to improve their proficiency in the speaking skill is gradually maturing into a malady The symptoms are evident, when the average graduate attends job interviews or try to become self-employed in urban areas, where a minimum level of communicative ability in English is expected. Apparently, to make up for the deficiencies in the existing undergraduate English classroom, several Spoken English Institutes have mushroomed, who claim to provide quick remedies, with high fees, to the desperate job seeker.